Association of aLDFA with functional outcome of distal femur fracture treated with locking plate - Singh, Ajeet; Kumar, Rakesh; Ranjan, Rajni; Mahajan, Avijit; Ahmad, Nadeem (International Journal of Research in Orthopaedics, 2018)
Background: Distal femoral fracture is one of the common presentations in orthopaedic emergency. Stable fixation and early mobilization is necessary to avoid knee stiffness with maximum functional outcome. We have done a retrospective analysis of Type 33A (supracondylar) and type 33C (supraintercondylar) fracture with distal femoral locking plate. Close observation done by aLDFA for varus collapse and functional outcome. Methods: 61 patients of Type 33A (supracondylar) and Type 33C (supraintercondylar) treated from January 2011 to august 2016 selected for the study. Functional and radiological outcome of fracture assed by mize criteria and aLDFA respectively. Most of the cases of Type 33C shows some amount of varus collapse specially type 33C3. Results: 6 out of 8 patients treated with type 33C3 treated with isolated distal femoral locking plate showed varus collapse more than 10 associated with implant failure and non union. Conclusions: Type 33C3 subset required a special consideration like dual plating or cortical strut graft on first go. aLDFA is strong predictor of for functional and radiological outcome.